Explaining the model of family performance based on love through the mediation of psychological security between couples - Ketabzadeh Badr, Tahereh; Hosseini, Saeedeh; Arefi, Mokhtar; Kakabaraei, Keyvan; Chehri, Azita (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The family, as the most stable social unit, is an essential axis for the healthy functioning of individuals and society. The purpose of this study was to explain the model of family performance based on love mediated by psychological security between couples. Methods: The present research is applied in terms of purpose and is classified in the group of descriptive-survey research in terms of data collection method. The statistical population includes all married men and women in areas 1 and 3 of Tehran in 1400-99. Sampling method was also available non-randomly. Data collection tools were demographic information questionnaire, mental security questionnaire (short form), family performance assessment questionnaire (FAD) and love questionnaire. In addition to descriptive statistics, data analysis was performed using AMOS program. Results & Conclusion: The results showed that there is a significant relationship between the components of love and family functioning, there is a significant relationship between love and psychological security, there is a significant relationship between psychological security and family functioning, psychological security in the relationship between love and Family functioning plays a mediating role.